Sedimentary History of Trace Metals Over the Past Half-Century in Songkhla Lake, Western Coast of the Gulf of Thailand: Anthropogenic Impacts and Contamination Assessment - Dong, Ke; Qiao, Shuqing; Wu, Bin; Shi, Xuefa; Chen, Yufei; Shan, Xin; Liu, Shengfa; Kornkanitnan, Narumol; Khokiattiwong, Somkiat (Frontiers in Earth Science, 2021)
Coastal lagoons are among the most vulnerable and economically significant ecosystems on Earth. Songkhla Lake, connected with the Gulf of Thailand, is the second largest lake in Southeast Asia and supports the development of the fishery, transportation and tourism industries in southern Thailand. With increasing anthropogenic disturbances, the lake is facing acute ecological problems and further research is needed. Here, we provide 55-year record of grain size, color reflectance, magnetic susceptibility, total organic carbon, total nitrogen and trace elements (As, Hg, Pb, Cr, Ni, Cu, and Zn) concentrations of sediment core SKL8-2 collected from Songkhla Lake. These records reveal a three-stage sedimentary and input history of trace metals under anthropogenic effects: (1) From 1964 to 1982, it was a natural terrigenous input period with a relative reduction environment when the channel connecting Songkhla Lake and the Gulf of Thailand was closed. (2) Trace metal concentrations, organic carbon content, b* value, and magnetic susceptibility changed abruptly in 1982. During 1982-2000, the sources of trace metals were more complex than during 1964-1982, and mainly came from urban wastewater, industrial effluent and fishery discharge. (3) From 2000 to 2019, contamination signals of Pb, Hg, As, Zn, and Ni emerged in the first decade because of the rapid development and poor sewage treatment around nearby cities.